2016
DOI: 10.1007/s11033-016-4062-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromogenic media for MRSA diagnostics

Abstract: For the past decade, a number of chromogenic media for methicillin-resistance Staphylococcus aureus (MRSA) detection have been developed and applied, including Oxoid Brilliance™ MRSA, CHROMagar™ MRSA, BBL™ CHROMagar™ MRSA, MRSASelect and chromID MRSA. The advantages of these chromogenic media offers direct detection of visible staphylococcal colonies, coupled with the use of chromogenic enzymatic substrates that can be hydrolyzed by S. aureus to confirm species or strain identification. BBL™ CHROMagar™ MRSA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Chromogenic media have been preferred because they are faster than conventional methods and appropriate to use statistically according to many articles in the literature (Xu et al, 2016, Malhotra-Kumar et al, 2008, Sürücüoğlu et al, 2011, Denys et al, 2013. There are many studies that have investigated whether various chromogenic media are comparable and suitable for use (Strulens et al, Uzun et al, 2013, Cesur et al, 2014Von Eiff et al, 2008, Denys et al, 2013 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromogenic media have been preferred because they are faster than conventional methods and appropriate to use statistically according to many articles in the literature (Xu et al, 2016, Malhotra-Kumar et al, 2008, Sürücüoğlu et al, 2011, Denys et al, 2013. There are many studies that have investigated whether various chromogenic media are comparable and suitable for use (Strulens et al, Uzun et al, 2013, Cesur et al, 2014Von Eiff et al, 2008, Denys et al, 2013 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies revealed that the use of chromogenic media for MRSA identification can generally, provide acceptable diagnostic performance, although specificity and sensitivity of chromogenic media varies amongst suppliers. The performance of chromogenic media is influenced by several variables, including specimen type, incubation time, broth enrichment step, or investigator perception (Xu Z, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most methods used so far for the detection of bacterial pathogens rely on microbial culture on selective or chromogenic media (Xu et al . ), ELISA immunoassays (Yazdankhah et al . ), selective gene amplification and detection (Tombelli et al .…”
Section: Whole‐cell Detection With Biosensors Dedicated To S Aureusmentioning
confidence: 99%
“…Effective IPC implementation requires the rapid detection of MRSA. Traditionally, this has been achieved using selective growth media containing methicillin or cefoxitin, salt and a chromogenic substrate (for an overview, see (8)). The latter facilitates the quick differentiation of MRSA from other, clinically less relevant staphylococcal species that may also harbour mec genes.…”
Section: Introductionmentioning
confidence: 99%